Tcf4 Controls Neuronal Migration of the Cerebral Cortex through Regulation of Bmp7 - Chen, Tianda; Wu, Qinwei; Zhang, Yang; Lu, Tianlan; Yue, Weihua; Zhang, Dai (Frontiers in Molecular Neuroscience, 2016)
Abstract Background: Transcription factor 4 (TCF4) is found to be associated with schizophrenia. TCF4 mutations also cause Pitt-Hopkins Syndrome, a neurodevelopmental disorder associated with severe mental retardation. However, the function of TCF4 during brain development remains unclear. Results: Here, we report that Tcf4 is expressed in the developing cerebral cortex. In utero suppression of Tcf4 arrested neuronal migration, leading to accumulation of ectopic neurons in the intermediate zone. Knockdown of Tcf4 impaired leading process formation. Furthermore, Bone Morphogenetic Protein 7 (Bmp7) is upregulated in Tcf4-deficient neurons. In vivo gain of function and rescue experiments demonstrated that Bmp7 is the major downstream effector of Tcf4 required for neuronal migration. Conclusion: Thus, we have uncovered a new Tcf4/Bmp7-dependent mechanism underlying neuronal migration, and provide insights into the pathogenesis of neurodevelopmental disorders.